Family Portrait - George Karger, free-lance LIFE magazine photographer at this time:::Creator::::::::::::
John and Gwyn Steinbeck pose with baby Thom for a family portrait with an unknown couple, probably taken at Steinbeck'' East Fifty-First Street apartment in New York. John grew the beard in imitation of the motorized torpedo boat crews that he served with during the 1939-1945 war. Original in safe